Money, Money, Money: A Developmental Guidance Approach - Allan, John; Klassen, Garry (Canadian Journal of Counselling and Psychotherapy, 2008)
This article describes a developmental guidance unit on the topic of money. Grade six and seven students in a rural district brainstormed topics for guidance and ranked money concerns highest followed by boy-girl issues, hunting, hobbies, homework and teachers. Using a class discussion format (Allan 8c Nairne, 1989), two sessions were spent helping students explore, understand and develop coping skills regarding money issues. The findings indicate that students (a) worry about money, (b) understand why people overspend, and (c) develop wavs of eaming and saving money. The effects of the project on counsellor-teacher relationship are discussed.